Skeletal muscle carnitine loading increases energy expenditure, modulates fuel metabolism gene networks and prevents body fat accumulation in humans - Stephens, Francis B.; Wall, Benjamin T.; Marimuthu, Kanagaraj; Shannon, Chris E.; Constantin-Teodosiu, Dumitru; MacDonald, Ian A.; Greenhaff, Paul L. (Wiley, 2013)
Twelve weeks of daily L-carnitine and carbohydrate feeding in humans increases skeletal muscle total carnitine content, and prevents body mass accrual associated with carbohydrate feeding alone. Here we determined the influence of L-carnitine and carbohydrate feeding on energy metabolism, body fat mass andmuscle expression of fuel metabolism genes. Twelve males exercised at 50% maximal oxygen consumption for 30 min once before and once after 12 weeks of twice daily feeding of 80 g carbohydrate (Control, n=6) or 1.36 g L-carnitine+80 g carbohydrate (Carnitine, n=6). Maximal carnitine palmitolytransferase 1 (CPT1) activity remained similar in both groups over 12 weeks. However, whereas muscle total carnitine, long-chain acyl-CoA and whole-body energy expenditure did not change over 12 weeks in Control, they increased in Carnitine by 20%, 200% and 6%, respectively (P<0.05). Moreover, body mass and whole-body fat mass (dual-energy X-ray absorptiometry) increased over 12 weeks in Control by 1.9 and 1.8 kg, respectively (P<0.05), but did not change in Carnitine. Seventy-three of 187 genes relating to fuel metabolism were upregulated in Carnitine vs. Control after 12 weeks, with ‘insulin signalling’, ‘peroxisome proliferator-activated receptor signalling’ and ‘fatty acid metabolism’ as the three most enriched pathways in gene functional analysis. In conclusion, increasing muscle total carnitine in healthy humans can modulate muscle metabolism, energy expenditure and body composition over a prolonged period, which is entirely consistent with a carnitine-mediated increase in muscle long-chain acyl-group translocation via CPT1. Implications to health warrant further investigation, particularly in obese individuals who have a reduced reliance on muscle fat oxidation during low-intensity exercise.